PENINGKATAN HASIL BELAJAR MATERI TUMBUHAN MENGGUNAKAN MEDIA WARDWALL PADA MATA PELAJARAN IPAS KELAS IV - Rico Ardiansyah; Ike Yusda Andriani; Bambang Eko Hari Cahyono (STKIP Subang, 2024)
The need for learning media is very important for educators, especially in explaining large and complex material. The lack of interest of students regarding understanding material regarding complex concepts such as plant materials in science and science lessons really requires better learning media to digest understanding of the material. The aim of this research is to include the application of Wardwall media for students to understand the plant material in science and science subjects for class IV elementary school, using the form of PTK research. The research took place at SDN 01 Winongo, Madiun city, through this it is hoped that it can provide the development of learning media to achieve learning objectives